ANTHROPOLOGICAL APPROACHES TO COGNITIVE LINGUISTICS: THE CONNECTION BETWEEN CULTURE AND LANGUAGE - Sobirjonova Mukhlisa Sobirjonovna (Western European Studies, 2024)
This article discusses how three traditional approaches to anthropological linguistics, namely Boaz linguistics, ethnosemantics, and discourse ethnography, can be applied to cognitive linguistics. The interrelationship between language and culture, how culture is represented through linguistics and cognitive sciences, as well as cultural cognition, cultural concepts, and cultural metaphors are analyzed. Important points are made about the approaches of anthropological approaches to the study of culture and language, the cultural values expressed in language, and their cognitive properties. The study includes analytical tools necessary for a deeper understanding of the interaction between language and culture
Keywords: Cognitive linguistics; anthropological linguistics; culture and language